Aortic Aneurysm and Horseshoe, Kidney - Estefan, Alberto; Abó, Juan C; Gateño, Nisso; Chifflet, Juan; Clark, Omar (Cirugía del Uruguay, 1977)
A case cf horseshoe aneurysm of abdominal. aorta and kidney causes the author to review existing literature on this condition. Preoperatory diagnosis of this infrequent lesiona! association can only be ·made through excretion urography, aortography or isotopic nephrogram. Each case of this ¡¡ssociation, presents an individual problem. Sectioning of renal isthmus should not constitute a systematic procedure, and should only be performed either to improve exposure or far vascular reasons'. Surgical tactics depend on the type of renal malformation . vascularization and of origin of aortic axis of arteries leading to kidney.